2010
DOI: 10.1089/ten.tea.2010.0103
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Biochemical Assessments of Three-Dimensional Poly(1,8-Octanediol-co-Citrate) Scaffold Pore Shape and Permeability Effects onIn VitroChondrogenesis Using Primary Chondrocytes

Abstract: Poly(1,8-octanediol-co-citrate) (POC) is a biocompatible, biodegradable elastomer with potential application for soft tissue applications such as cartilage. For chondrogenesis, permeability is a scaffold design target that may influence cartilage regeneration. Scaffold permeability is determined by many factors such as pore shape, pore size, pore interconnectivity, porosity, and so on. Our focus in this study was to examine the effects of pore shape and permeability of two different POC scaffold designs on mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…The results (113) demonstrate that POC can outperform other biodegradable elastomers used for cartilage tissue engineering and warrants further in vivo studies. Motivated by their previous studies, these researchers published successive reports to evaluate the coupled effects of 3D POC scaffold pore shape and permeability on chondrogenesis using primary chondrocytes in vivo (114, 115). The results indicated that low-porosity POC scaffolds composed of spherical pores showed a significantly greater increase in cartilage matrix formation over 6 weeks in vivo when compared with highly porous POC scaffolds composed of cuboidal pores.…”
Section: Applications In Regenerative Engineeringmentioning
confidence: 99%
“…The results (113) demonstrate that POC can outperform other biodegradable elastomers used for cartilage tissue engineering and warrants further in vivo studies. Motivated by their previous studies, these researchers published successive reports to evaluate the coupled effects of 3D POC scaffold pore shape and permeability on chondrogenesis using primary chondrocytes in vivo (114, 115). The results indicated that low-porosity POC scaffolds composed of spherical pores showed a significantly greater increase in cartilage matrix formation over 6 weeks in vivo when compared with highly porous POC scaffolds composed of cuboidal pores.…”
Section: Applications In Regenerative Engineeringmentioning
confidence: 99%
“…For example, thermoset POC elastomers were processed into foams using ordered hydroxyapatite molds. [99] In this technique, SFF methods are used to produce inverse wax molds. The wax molds are used to form sacrificial hydroxyapatite forms, which are then used to mold POC prepolymers.…”
Section: Ordered Assemblymentioning
confidence: 99%
“…Other authors observed the limited role of the macro pores in a PCL scaffold for bone regeneration and suggested further studies of the scaffold properties like interconnectivity and permeability 23 . In other works it is seen that a low permeability in a porous PCL scaffold enhanced chondrogenesis in vitro with primary chondrocytes 24 and by measuring the permeability of the scaffold with cells it is seen how the permeability diminishes from seeding as tissue grows 25 . Other authors have used 3D…”
Section: Introductionmentioning
confidence: 96%